Normatywna i rekonstrukcyjna perspektywa ujmowania metodologii badań w pedagogice - Urbaniak-Zając, Danuta (Kultura-Społeczeństwo-Edukacja, 2023)
The fundamental purpose of the article is to signal the premises for giving a greater importance to reconstructive methodology and to recall its possible dimensions (or generality levels of methodological research). The author begins by recalling the context of supplying the scientific method with a distinguished status, which justifies the dominance of the normative character of methodology in the researchers’ minds. She notes the importance of sociocultural factors for changes in the social sciences research practice, as well as the new understanding of practice by some contemporary philosophers, which justifies the granting of greater status to research practice. In the final part of the article, she presents levels of methodological reconstruction. Focusing on research practice will make it possible to see methodological innovations as a reaction to the change of conditions for conducting scientific research and as a search for ways to transcend the cognitive obstacles encountered.